2011
DOI: 10.1590/s0004-28032011000100016
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-induced intestinal mucositis delays gastric emptying and gastrointestinal transit of liquids in awake rats

Abstract: -Context -Methotrexate and other anticancer agents can induce intestinal mucositis, which is one of the most common limiting factor that prevent further dose escalation of the methotrexate. Objectives -To evaluate the gastric emptying and gastrointestinal transit of liquids in methotrexate-induced intestinal mucositis. Methods -Wistar rats received methotrexate (2.5 mg/kg/day for 3 days, subcutaneously) or saline. After 1, 3 and 7 days, sections of duodenum, jejunum and ileum were removed for assessment of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Previously, MTX-induced mucositis has been characterized by inflammation and increased expression and levels of MPO. 20) In the present study, high levels of MPO activity were also detected throughout the small intestines of the MTX-treated rats. Gastrointestinal toxicity due to MTX is largely due to the high rate of proliferation that enterocytes undergo, and the subsequent cell death that is induced by this pro-oxidant compound that depletes dihydrofolate pools.…”
Section: Discussionsupporting
confidence: 65%
“…Previously, MTX-induced mucositis has been characterized by inflammation and increased expression and levels of MPO. 20) In the present study, high levels of MPO activity were also detected throughout the small intestines of the MTX-treated rats. Gastrointestinal toxicity due to MTX is largely due to the high rate of proliferation that enterocytes undergo, and the subsequent cell death that is induced by this pro-oxidant compound that depletes dihydrofolate pools.…”
Section: Discussionsupporting
confidence: 65%
“…It has been reported that nimesulide prevents intestinal pathology induced with acetic acid and leukotriene in rats and decreases the activity of MPO which is a proinflammatory parameter [22]. Inflammation and increased MPO expression are important markers of intestinal mucositis [23]. Nimesulide has also been found to suppress MPO and significantly prevent the reduction of GSH that were increased in intestinal tissue created with burn [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a single dose of MTX is suffi cient in the development of ileal damage (24), together with villous atrophy, fl attening of the epithelium, crypt loss and restructuring of the crypts (9,26). Damage evaluation in intestinal mucosal revealed damage the 72nd h following MTX administration (22). In this study we evaluated ileal damage histopathologically and biochemically at the end of the 3rd day after MTX administration.…”
Section: Discussionmentioning
confidence: 97%
“…MTX is one of the most frequently used anti-metabolitic agents in clinical oncology. Clinical use is frequently accompanied by diarrhea and gastrointestinal symptoms (22,23). Ileal injury developing with the administration of MTX has been identifi ed in the literature (10,23,24,25).…”
Section: Discussionmentioning
confidence: 99%